Dampak Ekonomi Historis Krisis Malais : Perubahan Produksi dan Kesejahteraan Masyarakat Jepara (1930-1940) - Dhoni Frizky Aryasahab; Tamira Auga Abadi; Adinda Meyta Dwi Ayuningtyas (Universitas Negeri Semarang, 2025)
The Malayan Crisis (1930–1940), an extension of the global Great Depression, exerted a severe shock that devastated the foundations of the sugar industry in the Dutch East Indies. This research aims to provide an in-depth and detailed analysis of how this crisis impacted the structural changes in the sugar industry's production and the resulting consequences for the socio-economic welfare of the community in the Jepara Residency. The methodology employed is the Historical Method (encompassing heuristic, source criticism, interpretation, and historiography) combined with the Historical Economic Analysis approach, which effectively links the global phenomenon to its measurable local effects. Key findings of the research indicate a structural contraction within the sugar industry, quantitatively evidenced by a decrease in the number of operational factories from 11 to 8, alongside a significant reduction in the total area under sugarcane cultivation. This contraction had profound socio-economic implications, marked by extreme wage cuts for laborers, increased unemployment due to workforce reductions, the return of leased land to farmers, and most strikingly, the re-emergence of the barter payment system. This phenomenon of barter signals a devolution of the local monetary economy and a deep-seated purchasing power crisis. It is concluded that the Malayan Crisis effectively exposed the vulnerability of the colonial economic system, which was heavily reliant on a single export commodity, thereby compelling local communities to activate subsistence-based resilience strategies.